The Urgency of Written Evidence in Debt Transactions in the Perspective of Islamic Law - Widodo, Panggih; Abubakar, Achmad; Irham, Muhammad (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
Written evidence in debt transactions is increasingly needed in current credit activities to avoid various kinds of risks that might occur during the activity process. This needs to be studied in the perspective of Islamic law to find out the essence of the urgency of having written evidence in the view of Islam, either based on the verses of the Qur'an or with the opinion of the scholars on this matter. This research is a qualitative descriptive research and is a library research using primary and secondary data sources by examining various Islamic literature that talks about these matters, both classical and contemporary references. The results of this study are first, that debt is something that is not prohibited in Islamic religious teachings, but in practice it must be in accordance with Islamic law so that it does not eliminate the elements of mutual help and compassion in it. Second, the Qur'an explains that the existence of written evidence in debt transactions is something very important, so that the Qur'an provides rules for this and provides certain conditions for someone who makes such written evidence. In addition, to strengthen the position of written evidence, the Qur'an recommends having witnesses in a debt transaction. Islamic scholars have various opinions on the written evidence law. Some scholars say that it is not obligatory and some scholars say it is obligatory. The main purpose of such written evidence is to avoid any misunderstandings that may occur between the parties conducting these debt transactions at a later date regarding these debt transactions.